On 2,6,6-Trimethylcyclohex-2-Ene-1,4-Dione Biotransformation Beyond The Stationary Phase Of Baker’s Yeast Type III - Remlee, Mohd Ridzwan (Universiti Sains Malaysia, 2018)
The reduction of ketoisophorone by the whole cell, Baker’s yeast cell type II has been researched recently. One of the major product of the biotransformation reduction of 2,6,6- trimethylcyclohex-2-ene-1,4-dione (ketoisophorone) is (4R,6R)-4-hydroxy-2,6,6-trimethylcyclohexanone or also named as (4R,6R)-actinol using Saccharomyces cerevisiae in the present of glucose as the carbon source. The biotransformation of ketoisophorone (KIP) forms levodione also named as 6R-dihydro-oxoisophorone (DOIP), which is intermediate before further reduction into actinol (ACT). This experiment only focussed on the death phase of S. cerevisiae fermentation where the substrate, ketoisophorone(KIP) was introduced and the time duration of 22h of death phase which is started from 38th hour until 60th of fermentation of yeast cells. The availability and stability of cofactor, nicotinamide adenine dinucleotide (NADH) or nicotinamide adenine dinucleotide phosphate (NADPH) by the presence of glucose through Kreb’s cycle process was essential in the biotransformation of ketoisophorone during that phase was determined by the reading of absorbance using UV-Vis spectrophotometer. This work was also investigate the amount of substrate and intermediate present during 22 h of reaction in order to determine the activity of the two types of ezymes within the yeast cells which is responsible for this biotransformation which is carbonyl reductase (CBR) and enoate reductase (ER) to produce a chiral alcohol of (4R,6R)-actinol. The result showed that the death phase produced the intermediate as well as product which is actinol with the aid of cofactor availability during the reaction of biotransformation.